2018
DOI: 10.1016/j.kint.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational cohort study highlights kidney biopsy findings of lupus nephritis patients in remission who flare following withdrawal of maintenance therapy

Abstract: One of the most difficult management issues in lupus nephritis (LN) is the optimal duration of maintenance immunosuppression after patients are in clinical remission. Most patients receive immunosuppression for years, based mainly on expert opinion. Prospective data are unavailable. Complicating this issue are data that patients in clinical remission can still have histologically active LN; however, the implications of this are unknown. To study this, the Lupus Flares and Histological Renal Activity at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 17 publications
7
99
0
1
Order By: Relevance
“…These points aim to improve the design of clinical studies in order to answer clinically important questions, for which the current ‘state-of-the-art’ is insufficient. In particular, data regarding the optimal duration and timing of discontinuation of therapy in both renal and extrarenal disease are scarce;157 for the former, recent studies support the value of a repeat kidney biopsy for the management of maintenance therapy, but more data are needed 158 159…”
Section: Resultsmentioning
confidence: 99%
“…These points aim to improve the design of clinical studies in order to answer clinically important questions, for which the current ‘state-of-the-art’ is insufficient. In particular, data regarding the optimal duration and timing of discontinuation of therapy in both renal and extrarenal disease are scarce;157 for the former, recent studies support the value of a repeat kidney biopsy for the management of maintenance therapy, but more data are needed 158 159…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing histological activity was strongly predictive of a subsequent kidney flare when reducing immunosuppression. 103…”
Section: Monitoring and Prognosis Of Lnmentioning
confidence: 99%
“…Even if the nomenclature and definitions have not been used uniformly in studies of repeat kidney biopsies, several investigations have shown a discordance between clinical and histological outcome after the initial phase of immunosuppressive therapy for LN. More specifically, most studies reporting results from repeat biopsies have shown that residual renal activity may be evident in repeat biopsies from a considerable proportion of patients who have shown complete clinical responses to treatment, the latter mainly based on the proteinuric outcome 45–49. Again, as discussed above, haematuria levels have been demonstrated to yield weak or no correlations with activity components at the level of tissue in both initial and control kidney biopsies 23…”
Section: Histological Predictorsmentioning
confidence: 99%